Nickel-phenanthroline Complex Supported on Mesoporous Carbon as a Catalyst for Carboxylation under CO2 Atmosphere - Iman Abdullah; Riri Andriyanti; Dita Arifa Nurani; Yuni Krisyuningsih Krisnandi (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Carbon dioxide is a highly potential renewable C1 source for synthesis of fine chemicals. Utilization of CO2 in carboxylation reactions requires catalysts, such as: nickel complex for CO2 activation. However, the use of homogeneous catalysts in the reaction is still less efficient due to the difficulty of separating the product and catalyst from reaction mixture. Therefore, it is necessary to heterogenize the nickel complex in a solid support such as mesoporous carbon. In this report, mesoporous carbon (MC) prepared from phloroglucinol and formaldehyde through soft template method was used as a solid support for Ni-phenanthroline complex (Ni-phen). The catalyst was characterized by Fourier Transform Infra Red (FT-IR), X-Ray Diffraction (XRD), Scanning Electron Microscope - Energy Dispersive X-Ray (SEM-EDX), and Surface Area Analyzer (SAA). The result of SAA characterization showed that the pore diameter of MC was 6.7 nm and Ni-phen/MC was 5.1 nm which indicates that the materials have meso-size pores. Ni-phen/MC material was then used as a heterogeneous catalyst in the carboxylation reaction of phenylacetylene under an ambient CO2 pressure. The reactions were carried out in several variations of conditions such as temperature, time and catalyst types. Based on the results of the reaction, the best conditions were obtained at 25 °C for 8 h of reaction time using Ni-phen/MC catalyst.  Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).